Injection Anthrax—a New Outbreak in Heroin Users - Grunow, Roland (Deutscher Arzte Verlag, 2012)
BACKGROUND: Injection anthrax is a rare disease that affects heroin users and is caused by Bacillus anthracis. In 2012, there were four cases in Germany, one of which was fatal, as well as a small number of cases in other European countries, including Denmark, France, and the United Kingdom. Three cases among drug users occurred in Germany in 2009/2010, in the setting of a larger outbreak centered on Scotland, where there were 119 cases. CASE PRESENTATION AND CLINICAL COURSE: We present three cases of injection anthrax, two of which were treated in Regensburg and one in Berlin. One patient died of multi-organ-system failure on the day of admission to the hospital. The others were treated with antibiotics, one of them also with surgical wound debridement. The laboratory diagnosis of injection anthrax is based on the demonstration of the pathogen, generally by culture and/or by polymerase chain reaction, in material removed directly from the patient’s wound. The diagnosis is additionally supported by the detection of specific antibodies. CONCLUSION: Injection anthrax may be viewed either as an independent disease entity or as a special type of cutaneous anthrax with massive edema, necrotizing fasciitis in many cases, and about 30% mortality. It has appeared in recent years among heroin users in various European countries. In patients with suggestive clinical presentation and a history of heroin use, anthrax infection must be suspected early, so that the appropriate diagnostic tests can be performed without delay. Timely treatment can be life-saving. It is therefore important that physicians—and the individuals at risk—should be well-informed about this disease.